Ambient Assisted Living 8. AAL-Kongress 2015,Frankfurt/M, April 29-30. April, 2015 - Wichert, Reiner; Klausing, Helmut; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
In this book, leading authors in the field discuss developments of Ambient Assisted Living. The contributions have been chosen and invited at the 8th AAL Congress, Frankfurt/M. The meeting presents new technological developments which support the autonomy and independence of individuals with special needs. The 8th AAL Congress focusses its attention on technical assistance systems and their applications in homecare, health and care.
8th AAL Congress -- AAL-Kongress 2015 -- Health economy -- Assistive systems -- Patient record privacy -- Patient record security -- Individuals with special needs -- Telemonitoring -- Healthcare marketplace -- Medical care -- Health workforce.
Keywords: Biomedical engineering; Control engineering; Robotics; Automation; Geriatrics; Biomedical Engineering and Bioengineering; Control, Robotics, Automation; Geriatrics